What is Literature for? - Antoine Compagnon (Collège de France, 2014)
Along with the theoretical or traditionally historical question "What is literature?", the critical and political question "What can literature do?" begs an answer. What value do contemporary society and culture ascribe to literature? What utility? What role? "My confidence in the future of literature", wrote Italo Calvino, consists in the knowledge that there are things that only literature can give us, by means specific to it". Is this still relevant to us today?